2008
DOI: 10.1080/15287390802114808
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Exposure to Asian Dust Storm Events on Daily Pneumonia Hospital Admissions in Taipei, Taiwan

Abstract: In spring, windblown dust storms originating in the deserts of Mongolia and China travel to Taipei city. These occurrences are known as Asian dust storm (ADS) events. The objective of this study was to assess the possible associations of constituents of ADS with hospital pneumonia admissions of residents in Taipei, Taiwan, during the period 1996-2001. Fifty-four dust storm episodes were identified and were classified as index days. Daily pneumonia admissions on the index days were compared with admissions on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 43 publications
1
41
1
Order By: Relevance
“…The methods of measurement of PM 10 concentrations, based on samples from a variable number of in situ stations, are varied. For instance, beta-ray absorption (Chen et al 2004;Chen and Yang 2005;Cheng et al 2008), laser spectrometry (Perez et al 2008) and pump samplers (Wiggs et al 2003) have all been used. It is interesting to note that the levels are not automatically higher in Cat.…”
Section: Dust-health Relationship -Publication Datementioning
confidence: 99%
“…The methods of measurement of PM 10 concentrations, based on samples from a variable number of in situ stations, are varied. For instance, beta-ray absorption (Chen et al 2004;Chen and Yang 2005;Cheng et al 2008), laser spectrometry (Perez et al 2008) and pump samplers (Wiggs et al 2003) have all been used. It is interesting to note that the levels are not automatically higher in Cat.…”
Section: Dust-health Relationship -Publication Datementioning
confidence: 99%
“…A 10 µg/m 3 change in daily PM 10 was associated with an approximately 1% increase in cardiovascular and respiratory mortality in the Coachella Valley, California [16]. Dust storms in Taiwan had a 7.66% increase in the risk for respiratory diseases [17], congestive heart failure [8] and daily pneumonia hospital admissions [9]. Asian dust storms had a 4.1% increase in the rate of deaths from cardiovascular and respiratory causes in Seoul, South Korea [18] and a significant increase in respiratory hospitalizations in China [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Daily PM 10 levels over 200 µg/m 3 were suggested for small to medium scale dust events, while a higher cut-off point of 400 µg/m 3 was used to define severe dust events [5,6]. Other studies have used much lower PM 10 levels to identify dust storm days [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies of ASD in humans have shown that ambient ASD particles are associated with an increase in pulmonary (Bell, Levy, and Lin 2008;Chan et al 2008;Cheng et al 2008;Chiu et al 2008;Lai and Cheng 2008) and cardiovascular problems (Bell, Levy, and Lin 2008;Chan et al 2008;Yang, Cheng, and Chen 2009) and an increase in daily mortality in Korea (Hwang et al 2005;Kwon et al 2002;Lee, Son, and Cho 2007) and Taiwan (Chen et al 2004). The frequency and scale of dust events giving rise to ASD aerosols have increased rapidly in the east Asian region since 2000 (Mori et al 2003).…”
Section: Introductionmentioning
confidence: 99%